2019
DOI: 10.31223/osf.io/hs6t9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

More than planetary-scale feedback self-regulation: A Biological-centred approach to the Gaia Hypothesis

Abstract: Recent appraisals of the Gaia theory tend to focus on the claim that planetary life is a cybernetic regulator that would self-regulate Earth’s chemistry composition and climate dynamics, following either a weak (biotic and physical processes create feedback loops), or a strong (biological activity control and regulates the physical processes) interpretation of the Gaia hypothesis. Here, we contrast with the regulator interpretation and return to the initial motivation of the Gaia hypothesis: extending Schrödin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…[...] Hence, self-production by closure to efficient causation is more fundamental than self-regulation by feedback mechanisms." (Rubin & Crucifix, 2019) This opposes the viewpoint of a necessity of a "Gaia 2.0" as claimed by the French philosopher Bruno Latour and the British earth system scientist Timothy Lenton, who claim, "Gaia has operated without foresight or planning on the part of organisms, but the evolution of humans and their technology are changing that" (Lenton and Latour, 2018).…”
Section: The Gaia Hypothesismentioning
confidence: 96%
See 1 more Smart Citation
“…[...] Hence, self-production by closure to efficient causation is more fundamental than self-regulation by feedback mechanisms." (Rubin & Crucifix, 2019) This opposes the viewpoint of a necessity of a "Gaia 2.0" as claimed by the French philosopher Bruno Latour and the British earth system scientist Timothy Lenton, who claim, "Gaia has operated without foresight or planning on the part of organisms, but the evolution of humans and their technology are changing that" (Lenton and Latour, 2018).…”
Section: The Gaia Hypothesismentioning
confidence: 96%
“…The higher-dimensional geometry for the Earth is presenting an unifying view and thus contributing to current problems of representation in meteorology where scientists are calling for accurate maps of large regions of the sphere. The space model in GAIA 5.0 proposes 3-dimensional sub-spaces for the depiction of Gaia in contrast to current planar geoscience models which let them "keep shifting the tangent planes" as Rubin & Crucifix (2019) suggested it. For the first time Gaia is depicted as a hypersphere ( fig.…”
Section: The Gaia Hypothesismentioning
confidence: 99%
“…Numerous authors agree that autopoiesis is a plausible scenario for the instantiation of life organization on a planetary scale [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Recent work showed that this is plausible in a formal syntactic framework, using a proof-of-concept based on the chemical organization theory and the zero deficiency theorem applied on a simple but representative Earth molecular reaction network [ 18 ].…”
Section: The Autopoietic Complexity Of the Earth System Organizationmentioning
confidence: 99%
“…This is fitting for a mechanism that collects and distributes heat energy. of Gaia tend to make life the active participant that acts on climate but have largely limited that to cybernetic control (Rubin and Crucifix, 2019). The strong biological version of Gaia is guided internally by a regenerative network that leads to autopoiesis -self regeneration.…”
Section: Self-regulationmentioning
confidence: 99%